FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI MURID SDN 17 DI KECAMATAN KOTO VII SIJUNJUNG TAHUN 2017 - Rahmita Yanti (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Sijunjung Regency in 2014 - 2015, especially koto VII subdistrict shows the number of settling that is close to 10,83%. From the preliminary survey that the researchers conducted by Anthropometry according to BB / TB Index, it was found that the nutritional status of the students was less than 35.19%, Normal nutrition was 64.77%, it showed that the students' learning ability and nutritional status were quite low. This study aims to determine the factors associated with the nutritional status of students. The research design used was analytical with Cross Sectional Study approach. This research was conducted in SDN 17 Palaluar in Koto VII Sub-district of Sijunjung Regency and the time of research implementation in Mai - July 2017. The population in this research is all students of SDN 17 Palaluar in Kecamatan Koto VII Sijunjung Regency amounted to 210 people. Sampling technique done by simple random sampling. Data were collected using 2 x 24 hour food recall form and cheklist sheet. Univariate and bivariate data analysis using chi-square test. The results showed that 42.6% of children's nutritional status was abnormal, 39.7% less energy consumption, 48.5% less protein consumption, 57.4% of children did not have infectious diseases, 45.6% physical environment was not good, 63 , 2% food snack is not good, 51,5% food advertisement is not good. Statistically got relationship of energy consumption, protein, infectious diseases, physical environment, food snacks, food advertisement with nutritional status at student. It is hoped that Puskesmas will organize nutrition program of students through UKS (School Health Unit), so it can provide early information to schools about the importance of maintaining nutritional intake and nutritional status that can support student achievement. Schools can provide education and knowledge to school children about nutritious food. This research can be done by further researchers in elementary schools in other areas